Molecular epidemiology of rotaviruses during rotavirus vaccine introduction in Slovenia - Steyer, Andrej (Zdravniški vestnik, 2009)
Background Rotaviruses are the major cause of acute watery diarrhea in children up to 5 years of age. In 2007 and 2008 an extensive rotavirus molecular epidemiology study was conducted in Slovenia in order to provide information on rotavirus molecular epidemiology in our country. This study is part of the EuroRotaNet, European rotavirus surveillance study. Methods A total of 823 stool samples were collected from children with acute gastroenteritis in seven out of nine healthcare regions in Slovenia. The totalRNA was extracted and first amplification of VP7 and VP4 genes was performed in RT-PCR. The RT-PCR product was used for genotyping in multiplex-nested PCR. Untypable strains were included in sequence analysis of VP7 and VP4 genes. Results Genotype distribution similar to that in other European countries was observed. G1Pš8đ, G2Pš4đ, G3Pš8đ, G4Pš8đ and G9Pš8đ were the most prevalent genotypes in 2007 and 2008, except of G3Pš8đ, not detected in 2008. Relatively high rate of possible zoonotic strains was detected in 2007 (2.5%). The emerging unusual strain G10Pš14đ was the only potential zoonotic strain detected in 2007 and 2008. Conclusions After the vaccine introduction in Slovenia in 2007, no specific changes in molecular epidemiology of rotaviruses was observed. This finding was expected since rotavirus vaccine coverage in 2007 in Slovenia was very low. Genotype G1Pš8đ remains the most prevalent genotype. The rotavirus strain surveillance in Slovenia should be carried on to allow monitoring the spread of some unusual rotavirus genotypes, like G10. The G10 strains should be tracked especially invaccinated children as no data on vaccine efficiency against infectionwith G10 strains was presented till now.
Keywords: cepljenje; child; Child, Preschool; epidemiologija; Epidemiologija molekularna; Epidemiology, Molecular; Feces; Gastroenteritis; Genetics; genotipizacija; otroci; Otrok predšolski; Polimerazna, verižna reakcija; Polymerase Chain Reaction; Rotavirus; Rotavirus Infections; rotavirusi; Rotavirusne infekcije; Viral Vaccines; Virology; Virusna cepiva